Somatic and psychiatric symptoms of brain tumors - a review of the literature - Joanna Olszak; Karolina Zalewa; Dominika Orłowska; Lidia Bartoszek; Wojciech Kapłan; Karol Poleszczuk; Mikołaj Poleszczuk; Alicja Milewska; Anna Czuba (Kazimierz Wielki University, 2024)
Introduction and Purpose   Brain tumors cause a variety of somatic and psychiatric symptoms, which vary depending on the age of the patient and the location and type of tumor. Symptomatology includes both physical symptoms, such as headache, nausea, seizures and weakness, and psychiatric symptoms, including mood, personality and cognitive dysfunction. In children, the clinical picture is more complex and includes specific developmental difficulties. The purpose of this paper is to analyze the various symptoms accompanying brain tumors in order to detect them early and enable faster diagnosis.    Material and Methods   A comprehensive literature review was conducted using the PubMed database, focusing on articles published until the end of 2023.The search included the keywords: "brain tumors" "symptoms" "headache" and "psychiatric" in various combinations. Relevant studies were selected based on criteria such as somatic and psychiatric symptoms and early diagnosis of brain tumors.  Results   Accumulating data show the diversity of symptoms associated with brain tumors. Somatic symptoms such as headache, optic disc swelling, nausea, and seizures depend on intracranial pressure and tumor location. Psychiatric symptoms, including personality changes, mood disorders, and cognitive impairment, pose a significant diagnostic challenge in adult patients. In children, brain tumors can cause developmental delay and atypical neurological symptoms.   Conclusions  The symptoms of brain tumors are highly variable and difficult to diagnose, which significantly delays proper diagnosis of the disease. Its early detection is crucial as it improves the prognosis of patients, significantly improves their quality of life, and allows for the introduction of effective therapeutic interventions.